Sixty Years of Research on Polaritons: A Scientometric Review - R. Ruiz‐Sánchez; R. Arencibia‐Jorge; J. L. Jiménez‐Andrade; J. Tagüeña; H. Carrillo‐Calvet; Y. G. Rubo (Engineering Reports)
ABSTRACT In this scientometric review, we characterize the evolution of polaritonics research during the last 60 years. We explore how the understanding and utilization of polaritons lead to the development of advanced technologies. By employing networks, bibliometric analysis, and artificial intelligence techniques, we identify research trends, patterns of international collaboration, and key topics within the field. We combine bibliographic coupling techniques with a comprehensive literature review, with the aim of analyzing the evolution of the most important research fronts. Our study reveals an exponential growth of scientific output, with a high level of specialization in areas such as Optics, Applied Physics, Materials Science, Physics of Condensed Matter, Nanotechnology, and Electrical and Electronic Engineering. We use Self‐Organizing Maps to identify the variety of scientometric performance profiles of the most productive countries, as well as the evolution of the world's scientometric profile. In spite of being a research activity predominantly centered in Europe and the United States, the emergence of China during the last 10 years is remarkable. Our study highlights progress in understanding optical phenomena, excitations in specific materials, and the characterization of polaritons at interfaces and nanostructures, underscoring their potential for practical applications such as sensors and optical devices.